Fostering Collaboration and Enhancing Classroom Dynamics: Exploring Innovative Pedagogical Approaches at KGRCET - Sandhya, Tuti; Kakarla, Udaysri; Chandana, CH. (Journal of Engineering Education Transformations, 2025)
In the engineering workforce in the context of globalization, the demand has been growing for graduates not only technically but also possessing skills of collaboration and communication. This paper addresses the critical importance of collaborative learning in the education of engineers, laying an emphasis on the students' ability to develop appropriate communication skills that can be put into action in response to changing international and technologically advanced work environments. The interactions between global counterparts by engineering professionals require effective communication and teamwork. Hence, proficiency in these skills becomes crucial for the success of such professionals. This study focuses on the effectiveness of collaborative learning methods used in the classrooms of engineering, with a specific focus on final-year students at K.G.R.C.E.T, Hyderabad, India. It analyses the effects of these methods on the ability of students to perform in group settings and identifies the obstacles that create problems in effective communication. This work uses academic and industrial input to measure the value of communicative performance with regards to learning outcomes. Findings of the results suggest high student demand for engaged class interaction, which directly maps on to better communication competency and performance trends in this case study period. An underlying argument made by these results is the integration of collaborative learning into the existing engineering curricula to improve better preparation for the job of graduates based on increased modern workplace demands.